O acesso e a permanência dos alunos nas salas de recursos multifuncionais no contexto amazônico - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The school inclusion of students with disabilities, global developmental disorders and high skills / giftedness, the target audience of Special Education, has been ensured by legal instruments (BRASIL, 1988; BRASIL, 2008; BRASIL, 2009; BRASIL, 2011a; BRASIL, 2015a ) that guide the education systems and guarantee the offer of Specialized Educational Service (AEE) in Multifunctional Resource Rooms. These, despite having guaranteed access to regular education, suffer restrictions regarding to to their schooling processes due to the lack of knowledge of their learning characteristics, both in the common classes of regular education, and in specialized educational assistance, especially in regions far from large centers. Thus, the present study aimed to know how the access and permanence of the target students of Special Education in the Multifunctional Resource Room occurs, from the perspective of the teachers. Outlined by the Qualitative approach of a Descriptive character, the research sought to understand this reality in municipalities of the Microregion of the Madeira River, in the South of Amazonas: Humaitá, Manicoré, Novo Aripuanã, Apuí and Borba, which have a Multifunctional Resource Room (SRMs) under management of SEDUC-AM. AEE teachers were part of the research. For data collection, a semi-structured interview script was used. We analyzed the data from Descriptive Statistics and Content Analysis (BARDIN, 2009). In this study, we found, from the teachers' reports, difficulties regarding the access and permanence of these students in the SRM’s, mainly with the family, because the ways of approaching is not yet contributing for the family to perceive itself as an important part in the inclusion process. We perceive inclusive practice efforts, but most of the time, they are carried out only by the teachers of the AEE.
Keywords: Inclusão escolar; Educação inclusiva; Atendimento Educacional Especializado; Práticas inclusivas; Distúrbios da aprendizagem; CIÊNCIAS HUMANAS; Inclusão Escolar; Sala de Recurso Multifuncional; Acesso; Permanência